Pengaruh Pendidikan/Latihan, Dan Pembagian Kerja Terhadap Kinerja Pegawai Melalui Kepuasan Dan Motivasi Pada Dinas Sosial, Tenaga Kerja Dan Transmigrasi Kabupaten Klaten - Kasidin, Kasidin; Wiryani, Ratri (-)
The research conducted aims to determine: 1) the influence of the significance of education and training to the satisfication, 2) a significant effect on the motivation of education and trainig, 3) a significant influence on the satisfication of the division of labor, 4) a significant influence on the dicision of labor motivation, 5) significant influence of education and the exercise of employee performance, 6) a significant influence of education of the division of labor employees, 7) a significant effect on performance satisfication, 8) a significant effect of motivation on the performance of Sosial Service employee of Manpower and Transmigration Klaten.Keyword: Performance, Motivation, Satisfication,Division of Labour, and Education and Training.